LL-37, IL-36, GALECTIN-3 AND TLR-3 LEVELS IN IDIOPATHIC GRANULOMATOUS MASTITIS - Aydin, U.; Oz, B.; Karatas, A.; Gur, M.; Sagir, R. Piskin; Artas, G.; Koca, S. S. (Elsevier, 2020)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 03, 2020 -- ELECTR NETWORK